The Influence of Plagiarism Policy Implementation on the Quality of Academic Writing Among Postgraduate Students at the University of Dar es Salaam - Mislay, Moshi Amsi; Anania, Ahadi Mzumbwe (International Journal of African Higher Education, 2024)
Plagiarism policies have become an important feature of quality assurance practices in higher education institutions around the world, with a focus on improving the quality of academic writing and other research products. The University of Dar es Salaam (UDSM) purchased Turnitin software in 2015 to detect plagiarism in academic writing, including postgraduate theses, dissertations, term papers and assignments. This article examines the implementation of the university’s plagiarism policy using the case of postgraduate students’ theses and dissertations in selected academic unit (SAU). A sample of 556 postgraduate theses and dissertations submitted to SAU for plagiarism testing between January 2016 and December 2021 was collected, tested using Turnitin, and analysed to establish the trend and extent of plagiarism following policy adoption. Moreover, the study aimed to identify the limitations of using Turnitin to detect academic cheating among postgraduate students. The findings indicated that although the adoption of Turnitin software has reduced the trend in plagiarism in theses and dissertation writing, its effectiveness is limited because it fails to detect plagiarism levels within individual chapters of theses or dissertations. It is recommended that the plagiarism policy be reviewed to take into account new strategies that focus on individual chapters as well as the tolerance level of 30%, which seems high. Policies that address plagiarism content in postgraduate curricula should also be considered.